Essays on industrial agglomeration and location choice of foreign enterprises - LIU, Jianmin (2019)
This thesis examines the patterns of industrial agglomeration and its role in explaining the location choice of foreign enterprises in China, through several essays, that includes three empirical essays and two review and ‘theoretical grounding’ essays. It starts by first offering a review of industrial agglomeration and its measurement, highlighting issues in related literature in review essay 2. Then chapter/essay 3 sets out to measure industrial agglomeration using the Ellison-Glaeser (EG) index, which allows for a better understanding of the topic. The essay provides an in-depth analysis and is able to identify cluster patterns and its evolution over time. This type of analysis is carried out for industrial specialization of provinces and cities (regional perspective) and geographic concentration of industries (industry perspective), thus shedding light on questions of urbanization and localization. Essay 4 reviews the theories behind foreign direct investment (FDI) and multinational enterprises’ (MNEs) direct investment. This is followed by two essays, 5 and 6, which address the question of the role of agglomeration in the location decision of foreign enterprises in Chinese cities and one Chinese city, namely Ningbo, respectively. Essay 5 deploys various measures of industrial agglomeration drawing from essay 3. In particular, the EG indices used are both from city (industrial specialization and diversity) and industrial (geographic concentration and dispersion) perspectives, capturing urbanization and localization respectively. These are further deconstructed into foreign-specific industrial agglomeration and its domestic counterpart to connect location choice to the foreign industrial sector and the domestic one respectively, beyond a broad industrial structure level. Essay 6, with the notion of geographic scope in mind, focuses on the location decision of multinational firms in Ningbo and its drivers; emphasis on agglomeration – the cumulative/stock kind with spatial elements. The key findings of this thesis can be summed as follow: i) Both regional structure of industries and industrial structure in provinces are dispersed over time in China in most cases. ii) Natural advantages driven industries are more geographically concentrated. Labor-intensive manufacturing industries are more geographically concentrated than capital-intensive and technological-intensive ones. Industrially diversified provinces are concentrated in the eastern and coastal areas, while industrially specialized provinces are more concentrated in inland China. iii) A positive significant role of both domestic and foreign-specific industrial agglomeration in driving the location choice of MNEs with a preference for urbanization or industrial diversity by foreign enterprises when choosing a city, counter-balanced by the preference of new foreign firms for geographic concentration of industries iv) Foreign enterprises prefer both industrial diversity and geographic concentration, when concerned with foreign-specific industrial agglomeration. However, there is preference for industrial specialization and geographic dispersion when reacting to the broad industrial structure by the same foreign enterprises. v) Foreign-specific agglomeration – measured as the existing stock of foreign firms – matters as a whole, while domestic agglomeration matters in most cases except for the electronics industry. vi) The implicit tax rate has a positive influence on the decision to invest of MNEs, except for the electronics industry and rural areas. Market size, infrastructure, and public input spending do not seem to exert a significant influence on the location choice.